2015
DOI: 10.1007/s12328-015-0587-6
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of repeated cytology of pancreatic juice obtained by endoscopic nasopancreatic drainage tube for early diagnosis of pancreatic cancer: a case series including a case of carcinoma in situ

Abstract: Repeated cytology of pancreatic juice obtained by endoscopic nasopancreatic drainage (ENPD) tube has been highlighted as an early diagnostic method for small pancreatic cancer, including carcinoma in situ. We report two cases of early-stage pancreatic cancer diagnosed using repeated cytology; both cases underwent curative resection. No significant masses were found on conventional imaging in either case, with only pancreatic duct strictures being observed. ENPD tubes were placed to collect pancreatic juice in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…These histopathological changes may occur around high-grade PanIN lesions [30]. Other reports have also suggested that not only fibrosis, but also fatty changes, can contribute to the hypoechoic area around MPD stenosis [31,131]. A representative case of MPD stenosis surrounded by hypoechoic area with high-grade PanIN is shown with schema in Figure 2D.…”
Section: Hypoechoic Changes Around the Mpdmentioning
confidence: 89%
“…These histopathological changes may occur around high-grade PanIN lesions [30]. Other reports have also suggested that not only fibrosis, but also fatty changes, can contribute to the hypoechoic area around MPD stenosis [31,131]. A representative case of MPD stenosis surrounded by hypoechoic area with high-grade PanIN is shown with schema in Figure 2D.…”
Section: Hypoechoic Changes Around the Mpdmentioning
confidence: 89%
“…The cause of fibrosis is presumed to be focal pancreatitis, whereas cytokines, such as TGF-β, from cancer cells could cause fibrosis, as preparation for cancer cells to invade surrounding tissue [19]. On the other hand, there are cases without the hypoechoic area, even when the stricture was surrounded by fibrosis [14,20]. In our study, three cases of invasive carcinoma, classified as simple stricture type (A1) in the pancreatic head, were accompanied with fibrosis, but no fatty change of the parenchyma was recognized around the stricture.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it was shown in the study by Iiboshi et al [ 12 ] were 7 of 15 patients presenting with focal stenosis and distal dilatation of the main pancreatic duct and included in the ENPD placement group were diagnosed with carcinoma in situ . The cytology of pancreatic juice is a procedure which has attracted the attention in the eastern groups, particularly in Japan centers[ 13 - 15 ], however its practice is not extended in the western countries. Only one study from a western institution has been published focusing in the DNA methylation analysis in isolated but non-multiple samples of pancreatic juice obtained in intraoperative pancreatic resections or by ERCP intubation in non-operated on patients[ 16 ], still it only has reached a research interest and has not been expanded in clinical practice.…”
Section: Introductionmentioning
confidence: 99%